The use of social contingency in modifying the maladaptive behavior of a child at the Tahanan Special School (GABAY) - Cruz, Loreto Vales 1943- (College of Education, University of the Philippines Diliman, 1977)
This study is on the application of social contingency, a behavior modification technique, in managing and modifying the maladaptive behaviors of a child at the Tahanan Special School at the Manila Youth Reception Center. The suggested procedure is by Donald MacMillan, which was used to serve as a guide in applying the behavior management technique in the classroom. It was recommended in modifying behaviors of a disruptive child that can cause a general effect on the class.